The Impact of Air Pollution on the Physiological Vitality and Biodiversity of Forest Ecosystems - Hadi, Misbul; Saharani, Rahma Ayu; Harahap, Syahrul Pardamean; Prananta, Ichsan Ananda; Inem, Nauval Perdana; Akrama, Anif; N, Nashami (Penerbit Yayasan Daarul Huda Kruengmane, 2025)
This study aims to conduct an in-depth analysis of the impact of air pollution on forest ecosystem health and functioning, with a focus on identifying ecosystem sensitivity levels to major pollutants such as particulate matter (PM?.? and PM??), ozone (O?), sulfur dioxide (SO?), and nitrogen dioxide (NO?). Using a literature review approach with a quantitative–comparative method, this study compares forest conditions across different pollution levels through vegetation and soil sample data and statistical modeling. The results indicate that air pollution significantly affects plant physiology, including a reduction in chlorophyll content of up to 27% and canopy area by 18%, thereby inhibiting photosynthesis. In addition, a decline in biodiversity of 15–25% and an increase in forest fire frequency by up to 1.4 times were observed, associated with high levels of tropospheric ozone. Soil quality also showed degradation, with a pH decrease of 0.8–1.2 points and increased accumulation of heavy metals (lead increased by 35% and cadmium by 22%), disrupting nutrient cycling. This study emphasizes the importance of using bioindicators, such as mosses and insects, in monitoring forest health. These findings provide an evidence-based foundation for policy recommendations to support mitigation strategies and sustainable forest management in order to maintain ecosystem vitality amid global environmental pressures.